SOME DIMENSIONS OF INTEGRATED SYSTEMS. - Woods, Richard S. (The Accounting Review, 1964)
Abstract The structure of an integrated information system is difficult to define, and practical tests for its boundaries are evidently needed. This paper considers the organizational limits of such a system with- out detailed consideration of mechanization and its effects. One purpose is to make possible some initial decisions as to what systems and what organizational units might be encompassed in an initial plan for integration. The configuration is shown to be irregular and its limits are shown to be decided by pragmatic considerations. No attempt is made to enumerate all possible sub-systems that might be considered, although examples familiar to accountants have been furnished. Criteria are expressed in general terms, due to the varying information needs and problems of individual enterprises. The legal definition of a corporation is not considered to be adequate for defining the area over which an integrated system might be imposed. In addition, an attempt is made to relate sub-systems, and to define requirements for their integration. These requirements essentially are in terms of data processing compatibility (the usual subject of papers on "total" systems) and compatibility of like and unlike sets of data. The latter is obviously important and is frequently overlooked. In analyzing the links between sets of data, a study of intersections is considered to be helpful. The intersections reveal lack of structural compatibility in the organizational dimension (if it exists) and in addition make possible the identification of redundancies in the vertical dimension. Further analysis is required in the latter case, if unwarranted redundancies are to be eliminated.